A Putative Amidase Endolysin Encoded by Clostridium perfringens St13 Exhibits Specific Lytic Activity and Synergizes with the Muramidase Endolysin Psm - Hiroshi Sekiya; Maho Okada; Eiji Tamai; Toshi Shimamoto; Tadashi Shimamoto; Hirofumi Nariya (MDPI AG, 2021)
Clostridium perfringens is an often-harmful intestinal bacterium that causes various diseases ranging from food poisoning to life-threatening fulminant disease. Potential treatments include phage-derived endolysins, a promising family of alternative antimicrobial agents. We surveyed the genome of the C. perfringens st13 strain and identified an endolysin gene, psa, in the phage remnant region. Psa has an N-terminal catalytic domain that is homologous to the amidase_2 domain, and a C-terminal domain of unknown function. psa and gene derivatives encoding various Psa subdomains were cloned and expressed in Escherichia coli as N-terminal histidine-tagged proteins. Purified His-tagged full-length Psa protein (Psa-his) showed C. perfringens-specific lytic activity in turbidity reduction assays. In addition, we demonstrated that the uncharacterized C-terminal domain has cell wall-binding activity. Furthermore, cell wall-binding measurements showed that Psa binding was highly specific to C. perfringens. These results indicated that Psa is an amidase endolysin that specifically lyses C. perfringens; the enzyme's specificity is highly dependent on the binding of the C-terminal domain. Moreover, Psa was shown to have a synergistic effect with another C. perfringens-specific endolysin, Psm, which is a muramidase that cleaves peptidoglycan at a site distinct from that targeted by Psa. The combination of Psa and Psm may be effective in the treatment and prevention of C. perfringens infections.